The egg capsules and embryos of the patagonian gastropod Trophon plicatus (Lightfoot, 1786) (Caenogastropoda: Trophoninae) with remarks on the taxonomy of the southwestern atlantic Trophoninae - Pastorino, Roberto Santiago Guido (2014)
Fil: Pastorino, Roberto Santiago Guido. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "bernardino Rivadavia"; Argentina